The glass formation of a repulsive system with also a short range attractive potential: A re-interpretation of the free volume theory. (22nd November 2017) - Yuan, Guangcui; Cheng, He; Han, Charles C.
Abstract: In this feature article, we first make some simple reviews about the most popular theories for glass transition: 1) Free volume theory, 2) Entropy theory, 3) Götze's Mode coupling theory, and 4) Caging and Jamming theory. We address the issue of existing studies of glass transformations. Then, we review some special colloidal/polymer model systems which can give a repulsive potential together with an attractive potential and also large enough and slow enough, so we can study the structure (through microscopy and scattering techniques) and dynamics (mainly through rheology) changes as a function of temperature and volume fraction. We hope, this paper, with the study to explore the structural and dynamics along the path toward the equilibrium, can provide some information, stimulation, incentive, and guidance for future theoretical and experimental studies for glass transition of structural materials, especially for polymers, colloids and colloid/polymer systems. Graphical abstract: Highlights: The most popular theories for glass transition are reviewed. The issues of existing studies of glass transformations are addressed. The researches on some special colloidal/polymer model systems with a repulsive potential together with an attractive potential are illustrated. The ways to handle the true dynamics of structural glass formation are proposed and discussed.